PREDIKSI PARAMETER-PARAMETER BIOFISIK TANAMAN PADI DARI DATA GROunDSPECTROmETER DAN HYPERSPECTRAL PESAWAT TERBANG DENGAN MENGGUNAKAN TEKNIK PARTIAL LEAST SquARE REGRESSIOn (PLSR) DAN nORmALIzED DIFFEREnCE SPECTRAL InDEx (NDSI) - Darmawan, Arief; Hariyanto, Teguh; Sukojo, Bangun Muijo; Sadly, Muhamad (Jurnal Teknologi Lingkungan, 2011)
Paddy rice canopy hyperspectral was measured by using ground-based spectroradiometerÃ‚Â and HyMap sensor onboard an airplane from 350 nm up to 2500 nm in the same timethat covered various growth stages. Coinciding with hyperspectral measurement,Ã‚Â biophysical parameters such as leaf area index (LAI), SPAD value were measured onground during the airplane passed over area of interest (AOI). Rice yield was measuredÃ‚Â at the time of final harvesting by random selected yield (ubinan method) for eachÃ‚Â sampling area. In finding the best correlation among canopy hyperspectral reflectanceÃ‚Â with crop development, optimal individual waveband explored with involving all possibleÃ‚Â waveband combinations to obtain the best fitted two-pair waveband related to cropÃ‚Â biophysical parameters. Normalized Difference Spectral Index (NDSI) was appliedfrom spectral transformations (obtained from optimal waveband selected by exploringÃ‚Â all possible waveband) to improve sensitivity analysis on plant. Canopy hyperspectralprovided information about plant, soil and water background when plant canopy donÃ¢â‚¬â„¢tÃ‚Â completely cover soil surface yet. The present study was directed to examine spectralindices and establish the relationships between biophysical parameters of rice by usingÃ‚Â partial least square regression (PLSR) technique.Ã‚Â